1987
DOI: 10.1161/01.hyp.9.6_pt_2.iii206
|View full text |Cite
|
Sign up to set email alerts
|

The area postrema in deoxycorticosterone-salt hypertension in rats.

Abstract: SUMMARY Ablation of the area postrema in rats prevents sustained hypertension during angiotensin II infusion and after unilateral renal artery constriction (two-kidney, one clip hypertension). The current experiment was performed to determine whether an intact area postrema is required for hypertension development in a low renin model of experimental hypertension in rats. In 11 rats, the area postrema was destroyed using electrical current; the extent and specificity of each lesion was confirmed later by blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Brain lesioning studies have shown that the central nervous system may play a role in mineralocorticoid hypertension. For example, experimental lesions of the area postrema prevent hypertension 25 while leaving peripheral responses (vascular hyperreactivity) to DOCA intact. 26 Ablation of the anteroventral third ventricle 27 can abolish both the development of DOCA hypertension and the enhancement of peripheral vascular reactivity.…”
Section: Wistar-furth Ratsmentioning
confidence: 99%
“…Brain lesioning studies have shown that the central nervous system may play a role in mineralocorticoid hypertension. For example, experimental lesions of the area postrema prevent hypertension 25 while leaving peripheral responses (vascular hyperreactivity) to DOCA intact. 26 Ablation of the anteroventral third ventricle 27 can abolish both the development of DOCA hypertension and the enhancement of peripheral vascular reactivity.…”
Section: Wistar-furth Ratsmentioning
confidence: 99%
“…3 These data suggest that APX may interfere with an action of DOC-salt to modulate sympathetic outflow.…”
Section: Discussionmentioning
confidence: 93%
“…Details and results of this protocol have been described previously. 3 Four treatment groups of rats were studied: APX, DOC-salt; sham lesion, DOC-salt; APX, control; and sham lesion, control (n = 5/group).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations